Sistem Informasi Navigasi Wisata Kota Jakarta untuk Menentukan Rute Tercepat Menggunakan Algoritma Dijkstra Berbasis Web - Muhammad Rizki Syaumi; Achmad Noeman; Siti Setiawati; Prio Kustanto (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to design a web-based tourism navigation information system using Dijkstra’s algorithm to determine the fastest rout in Jakarta City. The proposed navigation system assists tourist in planning their trips more efficiently by providing real-time information on the fastest routes, travel distances, and estimated traviel times. By implementing Dijkstra’s algorithm, the system calculates the optimal route based on the starting location from the user’s device and destination data stored in the database. This research employs the waterfall system development method, which inludes the stages of analysis, design, implementation, and testing. The testing results demonstrate that the system accurately provides the fastest routes, enhancing convenience and travel efficiency for tourist.